2015
DOI: 10.4028/www.scientific.net/msf.821-823.632
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Minority Carrier Lifetime in Epitaxially Grown p<sup>+</sup>-p<sup>–</sup>-n<sup>+</sup> 4H-SiC Drift Step Recovery Diodes

Abstract: In this paper we report on the effect of temperature and injection level on the effective lifetime of non-equilibrium charge carriers in p-base of 4H-SiC PiN diodes. Studies were carried out on 1kV drift step recovery diodes (DSRDs) with p+-p--n+. The lifetime of non-equilibrium charge carriers in 4H-SiC p+-p--n+ structures increases by an average of 6 times from 250ns to 1.4μs with the increase of the samples temperature from 300K to 673K. However, increase of the injection level in the drift region from 2.3·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The single die DSRDs have mesa-diode geometry; their parameters and the details of fabrication are described in [3,4]. The measured lifetime of non-equilibrium charge carriers was 0.25µs at room temperature [4].…”
Section: Simulation Of 4h-sic Dsrdmentioning
confidence: 99%
See 1 more Smart Citation
“…The single die DSRDs have mesa-diode geometry; their parameters and the details of fabrication are described in [3,4]. The measured lifetime of non-equilibrium charge carriers was 0.25µs at room temperature [4].…”
Section: Simulation Of 4h-sic Dsrdmentioning
confidence: 99%
“…In [2,3] it has been experimentally established that silicon carbide based DSRDs can provide 2-4 times higher switching speed as compared to silicon devices and can handle switching current densities of up to 5•10 3 A/cm 2 . In [4] it has been shown that the 4H-SiC DSRDs as single dies are promising components for sub-nanosecond pulse generators for voltages of up to 2 kV. Higher operating voltages in the range of 5-10 kV could be achieved by fabricating single diodes with increased drift region thickness w = 60-120 µm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Carrier lifetime measurements were carried out on the falling edge of the post-injection EMF using the open circuit voltage decay (OCVD) method as described in [9]. The effect of fast neutron irradiation on measured lifetimes is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2003 [ 10 ], I. V. Grekhov et al reported a SiC DSRD with an area of 2.2 × 10 −3 cm 2 , which can output a voltage with a rise time of about 4 ns and a pulse amplitude of 400 V. In 2012 [ 11 ], P. A. Ivanov et al fabricated devices with an area of 3.9 × 10 −3 cm 2 which can output a voltage with a rise time of 2 ns. In 2015 [ 12 ], A.V. Afanasyev et al reported that a SiC DSRD with a breakdown voltage of 1 kV and an active area of 1 × 10 −2 cm 2 , which can output a pulse voltage with an amplitude of 1125 V and a rise time of fewer than 2 ns.…”
Section: Introductionmentioning
confidence: 99%